(3SDGdGJ CHj YHO Gddg GdMGce GdfjSCHhQi dCHi GdMSf Ydi Hf YeQ GdOGQbWfi Yf eTGjN Cgd GdYQGb Ydi GdMGce CeQge aj GdLQM hGdJYOjds - (3Ydj Hf YeQ Hf CMeO Hf egOj, CHh GdMSf GdqOGQbWfqj GdTGaYqj,J (B385 (3g` s ((3CHh HcQ Hf Ydi Hf ESeGYjd GdCfUGQj GdHgfSj GdTGaYj s)
(3ChdgG (B:s
(3CNHQfG GdTjN CHh HcQ YHO GdYRjR Hf CMeO Hf YeQ Hf jGbG GdHZOGOi HbQCJi Ydjg HeUQ CfHCfG GdTjN CHh RQYg GdebOSj s
(3BNQgG (B:s
(3abGd EfeG TQHJ ef COGhJc jG YeQ abGd YeQ EfeG fLdOc Ydi GdScQ BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3Ydjg JYdjbg HGdgGeT HNW eMeO Hf CHj HcQ GdOGhOj GdeGdcjs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
Keywords: (3GdMOjK h GdeUWdMs